Giant Tricholemmal Squamous Cell Carcinoma with Cranial Infiltration - Wollina, Uwe (Matrix Medical Communications, 2011)
Tricholemmal squamous cell carcinoma is a rare variant of squamous cell carcinoma thought to follow a more benign course. The authors present the case of a 67-year-old man with a giant tricholemmal squamous cell carcinoma on his scalp. Further investigations demonstrated a skull destruction and cranial invasion. Curative treatment was impossible, but tumor mass reduction and wound closure by sandwich split-thickness skin mesh graft transplantation using a dermal template was performed. Problems of advanced squamous cell carcinoma on the scalp are discussed.